An Observational Study of Suicide Deaths by Self-Poisoning with Opioids in Toronto (1998-2015). (August 2019) - Sinyor, Mark; Williams, Marissa; Gulati, Sanil; Schaffer, Ayal
Objective: Opioid self-poisoning is a common suicide method in North America. However, there is limited information about who dies by this method and whether legislation on opioid access has resulted in lower suicide rates by self-poisoning. The primary research question was whether the rate of suicide involving opioids has diminished since the implementation of Ontario's Narcotics Safety and Awareness Act (NSAA) (1998-2011 vs. 2012-2015). Methods: This study examined all suicides by intentional self-poisoning with or without an opioid in Toronto (1998-2015), and tested the mean change after NSAA by one-way ANOVA. Demographic and clinical characteristics as well as details surrounding the suicide were also compared for suicides by opioid and by non-opioid self-poisoning. Results: There were 773 suicides in Toronto by self-poisoning where the substance used was known (19.0% of all suicides). Of these, 289 (37.4%) had an opioid present and, in 249 (32.2%) suicides, the opioid was deemed to have been lethal. The mean number of yearly suicides involving opioids was 15.6 before and 17.5 after NSAA implementation (F 1.16, df 1, p = 0.30). Neither the rate per population nor the proportion of suicides by this method has changed between the 2 periods. People who died by suicide using an opioid had higher rates of pain, musculoskeletal, gastrointestinal/liver disorders, and cancer. Conclusions: This study confirms that opioids are a major contributor to suicide in Toronto, with no change in the rates after implementation of the NSAA. Physicians who prescribe opioids should monitor patients for elevated suicide risk and intervene where appropriate.